Kant's Theory of Simultaneity - Al-Fadli, Ageel (Université d'Ottawa / University of Ottawa, 2023)
In this thesis, I examine Kant's conception of simultaneity in relation to the idea of the empirical determinacy of time. I begin by introducing the concepts of time and simultaneity in Newton and Leibniz, and demonstrate how these two modern conceptions of time contributed to Kant's understanding of simultaneity and cosmological unity. It will be argued that Kant's conception of simultaneity was intended to account for the possibility of the rational determination of time, and that for this purpose, Kant sought to reinterpret the Principle of Sufficient Reason in his early writings by linking it to the simultaneity-relation between substances in reciprocal interaction, thus arguing for the possibility of coexistence between substances. This provides a way to understand how the unity of the world is fundamental to Kant's understanding of the rational determination of time and space. In Kant's critical period the relation of simultaneity is analysed as empirically realized through mutual interaction, but the pure manifold of time is thought to be intuitional, which requires the implementation of relational categories in order to be reproduced in experience. In the Third Analogy of the First Critique, the concept of mutual interaction is analysed in terms of balanced forces, which provides a means of describing the evolution of a dynamical system over time. It provides the process by which the connection between different dynamical systems is possible, and also for the synchronization of different clocks.
Keywords: Kant; simultaneity; Newton; time; Leibniz; Einstein; physics; Third Analogy; Community